Bilingualism and Heritage Language Maintenance: Parental Perspectives on French Educational Pathways in Australia - Norford, Victoria; Veliz, Leonardo (Paideia Revista de Educación, 2025)
This study examines the perspectives of parents of heritage speakers of French regarding educational options and pathways through the education system available to their children. Research into the educational choices and trajectories of heritage language learners has been identified as a significantly underexplored area. Data for this study was collected by means of an online questionnaire completed by 74 parents from across three states in Australia. Responses revealed parents’ strong impetus to educate their children in their heritage language but encountered difficulties in accessing services to support their heritage language learning goals. Key areas of concern included limited opportunities in in the early childhood and secondary education sectors and inappropriateness of curriculum options and teaching practices designed for foreign language learners. The study suggests a revision of curriculum options for heritage language learners and the creation of a dedicated syllabus for French which would align with offerings available for other languages.